O ensino de física utilizando elementos naturais como recurso pedagógico e laboratórios virtuais no 9° ano do ensino fundamental na Gleba de Vila Amazônia, Parintins – Amazonas - Fonseca, Maildson Araújo (2013)
Much has been said and written on improving physics teaching, introducing dynamic techniques and objective, appropriate methodology for the development of skills and attitudes, preparing the young to life. The years have passed and the tiredness is felt, and so seeks to reflect on the methodologies that are applied in teaching this discipline. This work describes the methodologies used in the field of Gleba Vila Amazonia, in the year 2012 and has as main purpose to show the use of field classes using natural resources, such as virtual lab and methodologies in educational practices in the discipline of physics, the use of experiments, are the most relevant and discussed. Were the ideas of pupils and teachers at the beginning and end of the teaching-learning process on the subject in question. Can't think of advance that students are interested in learning science, as we speak some authors. But contact with experience should wake up in them interest. In this way the results obtained prove that the use of these methodologies, will take students to verify the theory-practice in applied, getting results and significant stimuli.